Planning and Analysis of Integrated On-Grid Solar Power Plant using Pvsyst Software at the Krejengan Probolinggo Health Center - Dwi Nanda; Efendi S Wirateruna; Bambang Minto Basuki (Universitas Islam Malang, 2024)
The demand for electrical energy in Indonesia continues to increase significantly. The government has set a target of 23% of the New and Renewable Energy (NRE) mix by 2025, one of which is through the installation of Solar Power Plants (PLTS). This study aims to design and analyze the technical and economic feasibility of On-Grid Solar Power Plant at the Krejengan Health Center, Probolinggo, using PVsyst software. The solar PV system is designed to have a capacity of 6600 watts to meet the daily electricity needs of the health center. The simulations carried out show that this solar power plant is able to produce enough energy with high efficiency. Economic analysis using the Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Payback Period (PP) methods shows that this project is economically feasible. The implementation of this system provides significant economic benefits and contributes to the reduction of carbon emissions, in line with the national energy policy